Land cover change and land use suitability analyses of coastal area in Bantul District, Yogyakarta, Indonesia - SARAH AFSHOLNISSA (MBI & UNS Solo, 2019)
Abstract. Afsholnissa S, Hernawan E, Lastini T. 2019. Land cover change and land use suitability analyses of coastal area in Bantul District, Yogyakarta, Indonesia. Biodiversitas 20: 1475-1481. Shrimp farming in the southern coast of Bantul District is considered to be the cause of environmental degradation, decline of mangrove association due to logging for land conversion to shrimp pond and also considered to be the cause of agricultural land for crops around the shrimp pond. The purpose of this study was to identify land use change and analyze the land suitability for shrimp farming, agriculture, and mangrove plant associations. Identification of land use was done using ENVI 5.3. The study identified 34.88 ha (3.16%) empty ponds, 20.97 ha (1.90%) active ponds and as much as 91.93 ha (8.31%) land used for agriculture. The identification of land use change using Google Timelapse revealed a dominant land conversion of sandy soil and mangrove plant area into shrimp ponds in 2007 and continue to increase from 2011 to 2015. Land suitability was evaluated using ArcGIS 10.5 with an overlay method. The results revealed that 634.82 ha area of the land was suitable for shrimp ponds and ??84.32 ha area were suitable for non-paddy agriculture. Lands suitable for paddy field were about 148.58 ha, and that for mangrove plant association was 616.42 ha. Spatially, coastal area of ??Bantul District was dominantly suitable for shrimp farming.